Associations of work activities requiring pinch or hand grip or exposure to hand-arm vibration with finger and wrist osteoarthritis: a meta-analysis - Hammer, Paula EC; Shiri, Rahman; Kryger, Ann I.; Kirkeskov, Lilli; Bonde, Jens Peter (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVE ': 'We systematically reviewed the epidemiologic evidence linking finger and wrist osteoarthritis (OA) with work activities requiring pinch or hand grip or exposure to hand-arm vibration (HAV). ' ' METHODS ': 'PubMed and Embase databases were searched up to June 2013. We selected studies assessing the associations of radiographic diagnosed finger and/or wrist joint OA with work activities involving pinch or hand grip or exposure to HAV. We used specific criteria to evaluate completeness of reporting, potential confounding, and bias. Pooled odds ratios (OR) were computed using random-effects meta-analyses. ' ' RESULTS ': 'Of the 19 studies included, 17 were cross-sectional, 1 was a prospective cohort, and 1 a case–control study. The meta-analyses of studies that controlled their estimates for at least age and gender showed the associations of pinch grip work with proximal interphalangeal joint [OR 1.56, 95% confidence interval (95% CI) 1.09–2.23] and the first carpometacarpal joint OA (OR 2.10, 95% CI 1.06–4.17), but not with distal interphalangeal, metacarpalphalangeal, or wrist joints OA. Hand grip work and exposure to HAV were not associated with any finger or wrist OA. ' ' CONCLUSION ': 'Epidemiological studies provide limited evidence that pinch grip may increase the risk of wrist or finger OA, but causal relation cannot be resolved because of cross-sectional designs and inadequate characterization of biomechanical strain to the hand and wrist.
Keywords: degenerative joint disease; exposure; finger osteoarthritis; hand; hand grip; hand-arm vibration; manual work; meta-analysis; occupational exposure; osteoarthritis; osteoarthrosis; pinch; pinch grip; review; systematic review; wrist osteoarthritis